2013
DOI: 10.1098/rstb.2012.0407
|View full text |Cite
|
Sign up to set email alerts
|

‘It's the way that you look at it’—a cognitive neuropsychological account of SSRI action in depression

Abstract: The fact that selective serotonin reuptake inhibitors (SSRIs) have antidepressant effects in some patients supports the notion that serotonin plays a role in the mode of action of antidepressant drugs. However, neither the way in which serotonin may alleviate depressed mood  nor the reason why several weeks needs to elapse before the full antidepressant effect of treatment is expressed  is known. Here, we propose a neuropsychological theory of SSRI antidepressant action based on the ability of SSRIs to produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
134
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(144 citation statements)
references
References 51 publications
9
134
0
1
Order By: Relevance
“…Previous studies have shown MDD patients to exhibit hyperactivation in the amygdala to negative emotional and threatening stimuli (Harmer & Cowen, 2013). Being socially ostracized leads to significant discomfort, and individuals fear exclusion and rejection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown MDD patients to exhibit hyperactivation in the amygdala to negative emotional and threatening stimuli (Harmer & Cowen, 2013). Being socially ostracized leads to significant discomfort, and individuals fear exclusion and rejection.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that not receiving expected reward, or receiving unpleasant stimuli or events, can produce depression (Beck, 2008;Drevets, 2007;Eshel and Roiser, 2010;Harmer and Cowen, 2013;Price and Drevets, 2012;Pryce et al, 2011). More formally, in terms of learning theory, the omission or termination of a reward can give rise to sadness or depression, depending on the magnitude of the reward that is lost, if there is no action that can be taken to restore the reward (Rolls, 2013b(Rolls, , 2014a.…”
Section: A Non-reward Attractor Theory Of Depressionmentioning
confidence: 99%
“…However, the precise mechanism by which this occurs is critical to treatment strategies: while either impairment might lead to similar behavioral deficits, exactly which impairment a patient has carries implications for their treatment. At present, serotonin-targeting treatments are the first-line antidepressant method, but do not seem to alleviate depressive symptoms in many patients (Harmer and Cowen, 2013). After failed SSRI treatment, dopamine-targeting treatments can be attempted (Rush et al, 2006;Trivedi et al, 2006).…”
Section: Antidepressants: Repairing Representations?mentioning
confidence: 99%
“…It is true that we already have elegant emotional/cognitive accounts of depression (Harmer and Cowen, 2013), and there are many putative biological explanations of disruption and restoration at cellular (Castrén and Rantamäki, 2010) and molecular (Berman et al) levels. However, pharmacological level explanations often lose sight of the multidimensional nature of the depressive phenotype; and emotional or high-level explanations are difficult to relate directly back to the neurobiology.…”
Section: Free-energy: a Holistic Approach?mentioning
confidence: 99%